Valorisasi Bonggol Pisang dengan Polyol dan Kitosan Sebagai Bahan Baku Bioplastik - Berghuis, Nila Tanyela; Shelly, Rafkita; Ajipratama, Stanislaus Axel; Ar-Raihan, M. Hasbi; Wulandari, Oktaviani; Fitri, Ayu Silvia (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
Banana stumps, which are plentiful yet still underutilized, are one of the waste products of the banana harvesting process. Recent research indicates that banana stumps contain up to 76 percent starch. To address environmental issues brought on by the use of disposable plastics, we used starch from banana stumps as bioplastics feedstock. To enhance the performance of bioplastics, experiments with the addition of glycerol, sorbitol, and chitosan were conducted. FTIR spectra of the two bioplastic films indicate that additives do not alter the functional groups of bioplastics because they give equal absorption areas with just varying intensities. The result of the thermogravimetric analysis showed glycerol bioplastics disintegrated more quickly (231.85oC) than sorbitol bioplastics (278.75oC). The water absorption test reveals that glycerol bioplastics are more water-resistant than sorbitol bioplastics. According to the results of the biodegradation test, sorbitol bioplastics break down more quickly than glycerol bioplastics. The tensile strength test of sorbitol-based bioplastics yielded a value of 2.233 N/m2, which is greater than the glycerol-based bioplastics' value of 1.830 N/m2. These results show the banana stump's potential as a feedstock for the manufacturing of bioplastics.